How nanoinformatics could pave the way to safer design of engineered nanomaterials? - Saha, Sarmistha (Frontiers in Nanotechnology, 2025)
Applications of nanotechnology have rapidly expanded across various fields, including materials, energy, medicine, and the environment. The toxicity of nanomaterials (NMs) and nanotechnology to living organisms, as well as potential negative environmental impacts, poses significant challenges. Laboratory approaches for assessing the negative impacts of NMs are costly, time-consuming, and frequently fall behind the development of novel materials. Therefore, intelligent systems of informatics to forecast their toxicity potentials are a possible alternative option. Research on nanotoxicology has generated extensive and diverse datasets. However, data alone does not equate to information. Since little is known about how to extract meaningful information from large streams of data, a broad discussion of potential concerns still exists. In this regard, we present a perspective on how the “big data” can change the paradigm toward data-centric computational materials research to decipher the toxicity mechanisms of NMs for their efficient risk assessment management to provide safe-by-design standards for the sustainable advancement of nanotechnology. We will also discuss the challenges of the current data-driven research into the nano realm.